Cardiac abnormalities and skeletal muscle weakness in carriers of Duchenne and Becker muscular dystrophies and controls. - Grain, L; Cortina-Borja, M; Forfar, C; Hilton-Jones, D; Hopkin, J; Burch, M (2001)
Cardiac abnormalities, cardiomyopathy and skeletal muscle weakness have been described in female carriers of the Xp21 (Duchenne and Becker) muscular dystrophies (J Neurol 1975;209(4):279-285; Br Med J 1969;2:418-420; J AmMed Assoc 1996;275(17):1335-1338; Neurology 1980;30(5):497-501; Neuromusc Disord 1999;9:347-351; Arch Neurol 1989;46:673-675). We have screened volunteers from our Xp21 genetics register and found the prevalence of previously unrecognized, clinically relevant, abnormalities in this group to be less than previously reported. We studied 91 women (56 carriers and 35 controls), aged between 18 and 69 years, from our local population known to the Oxford Regional Genetics Register. Our study included controls, with the investigators being blind to the subject's genetic status. The prevalence of previously unrecognised cardiac abnormalities on echocardiogram and ECG was 18% (10/56). Seven percent (4/56) of carriers had cardiomyopathy, defined by significant LV dilatation and decreased shortening fraction. In most cases, subjects with abnormal cardiac findings were asymptomatic. Echocardiography was more frequently abnormal than electrocardiography, but in many subjects the measurements of left ventricular dimensions were only just outside the normal ranges. The prevalence of skeletal muscle weakness was 12% (7/56). It was usually recognized by the individual, although not previously volunteered, but was mild and did not substantially affect activities of daily living.